Assistance Systems in Manual Assembly - Hinrichsen, Sven; Riediger, Daniel; Unrau, Alexander (Production Engineering and Management)
Due to the continuing trend towards more complexity of products with an increasing number of variants and smaller lot sizes, the assembly often takes place -despite relatively high labor costs in Western industrialized nations -manually or partially automated. An outsourcing or relocation of assembly function abroad is not suitable in most cases.Therefore, it is increasingly important to reduce process variations and waste in manual assembly processes. Assistance systems have the potential, depending on the situation, to assist the worker in his work, to reduce error rate and to increase productivity. In a first part of the paper an overview will be given to different types of assembly assistance systems. Then a morphological chart is developed, which can provide assistance in selecting or comparing assembly assistance systems. With the help of this chart an assembly assistant system is presented. Finally a quick look is taken at further research being done in this area.
Keywords: Assistance systems; Manual assembly; Morphology